Clinical Significance and Risk Factors of Local Recurrence in Synovial Sarcoma: A Retrospective Analysis of 171 Cases - Zhang, Hongqiang; Huang, Wending; Feng, Qi; Sun, Wei; Yan, Wangjun; Wang, Chunmeng; Zhang, Jianing; Huang, Kai; Yu, Lin; Qu, Xinglong; Chen, Yong (Frontiers in Surgery, 2022)
Objective: To investigate risk factors of local recurrence of synovial sarcoma and the impact of local recurrence on survival. Methods: We retrospectively reviewed clinical data of patients with II to IIIB (AJCC8) synovial sarcoma who underwent surgery at our center between March 2005 to December 2016. Data relating clinicopathological factors, treatment and prognosis were collected. The impact of local recurrence on overall survival (OS), local recurrence-free survival (LRFS), and distant relapse-free survival (DRFS) were analyzed. The prognostic factors associated with local recurrence were also analyzed using Kaplan-Meier Curves and Cox regression analysis. Results: A total of 171 patients were included in this analysis. After a median follow-up of 48 months, 66 patients (38.6%) experienced local recurrence. The 5-year OS, LRFS, and DRFS rates of patients with local recurrence were 37.6%, 6.1% and 24.1%, respectively. Multivariate analysis showed that larger initial tumors, multiple recurrences, positive resection margins, marginal resection and lack of adjuvant therapy were associated with higher local recurrence. Conclusion: Local recurrence of synovial sarcoma is associated with distant metastasis and poor survival. Chemoradiation improves the prognosis of patients with local recurrence, in particular those for which recurrence occurs shortly after initial treatment.